The Potential Risks of Using Social Media: How Sharing Pictures with a Particular Pose Could Expose Biometric Data (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
The rapid expansion of social media has transformed communication, enabling seamless information sharing across global networks. While these platforms enhance connectivity, they also pose significant privacy risks, particularly through the unintended exposure of sensitive biometric data. Every day, billions of images are shared online, often revealing more information than users intend, including identifiable fingerprint details. This study examines how publicly available images can be exploited to extract biometric data using digital image processing and forensic analysis. By applying techniques such as contrast enhancement, noise reduction, and ridge pattern extraction, we assess the feasibility of retrieving fingerprint details from shared images. Findings highlight the potential risks of unauthorised biometric data collection, raising concerns about identity theft, unauthorised access, and financial fraud. The study emphasises the need for greater user awareness and advocates for stronger security measures, including automated detection tools, stricter privacy settings, and enhanced encryption, to mitigate the risks associated with biometric data exposure on social media.